Audit Tenure, Debt default dan Financial Distress pada Opini Audit Going concern - Hidayat, Taufik; Triwibowo, Edi; Fadlilah, Syifa (E-Jurnal Akuntansi; Vol 34 No 3 (2024)DO - 10.24843/EJA.2024.v34.i03.p20, 2024)
In a company's financial audit report, the statement given by an independent auditor is known as a going concern audit opinion. Several factors that can influence the continuity of a financial audit include audit tenure, debt default, and financial distress. The purpose of this research is to study how audit tenure, debt default, and financial distress impact the continuity of the auditor's business. The secondary data used in this research are the audited financial reports of manufacturing companies for 2018–2022. The total sample of 140 data from 28 companies that met the criteria was collected using the purposive sampling method. This study uses logistic regression analysis techniques. The results of this research indicate that audit tenure, debt default, and financial distress do not have a significant effect on going concern audit opinion. Keywords: Audit Tenure; Debt Default; Financial Distress; Opini Audit Going Concern